Examining the relationship between green mindfulness, spiritual intelligence, and environmental self identity: Unveiling the path to green entrepreneurial intention - Ali Saleh Alshebami; Mossab Saud Alholiby; Ibrahim A. Elshaer; Abu Elnasr E. Sobaih; Salem Handhal Al Marri (Administrative Sciences, 2023)
As inculcating green intention and behaviour among individuals, particularly potential entrepreneurs (students), has recently become a hot topic of discussion, it is essential to contribute to this debate by offering empirical evidence. Accordingly, the objective of this study is to examine how green mindfulness (GM) and spiritual intelligence (SPI) enhance environmental self-identity (ESI). This study also examined the role of GM and SPI in developing green entrepreneurial intention (GEI). The study investigated whether ESI could mediate the relationship between GM, SPI, and GEI. The study gathered information from 202 students at King Faisal University's Business Administration and Applied Colleges in Saudi Arabia using a self-administered questionnaire for these objectives. The study employed partial least-squares structural equation modeling to analyse the data. The study revealed some interesting findings. It was discovered that GM has a direct and significant positive association with ESI and GEI. Furthermore, it was also reported that SPI has a positive and significant connection with ESI, but no positive relationship with GEI. ESI revealed the existence of a meaningful positive relationship with GEI. Finally, when examining the mediating role played by the ESI, the study reported the inability of the ESI to mediate the relationship between GM and GEI. At the same time, it was able to fully mediate between SPI and GEI. The study provides a set of recommendations for policymakers and other stakeholders. The study is considered one of few studies investigating the key factors influencing GEI among students.
Keywords: 350; students; values; mindfulness; green business; intention